The craft of singing - Nair, Garyth (Plural Pub., 2007)
This is a new text with two principal aims: to provide a foundation of anatomical, physiological, acoustical and medical knowledge for students in the belief that one must know how something works before one can alter or repair it, and to carefully structure the learning of the foundational vocal skills necessary for real future development of each students technique past the end of the course. Borrowing from Voice Science but staying firmly centered in the studio or classroom, the text helps the reader with a raw vocal ability understand the function and care of their vocal instrument. In the second part, the book begins a carefully graduated approach to cement into place good singing habits. Three songs, comprising works in Italian, English and German, are used to produce exemplary vowels and consonants and wonderful songs. - Publisher.